PENYULUHAN PENCEGAHAN STUNTING BAGI MASYARAKAT UNTUK PERTUMBUHAN OPTIMAL ANAK DI KECAMATAN SOROPIA, KABUPATEN KONAWE - Yamin, Yamin; Fitrawan, La Ode Muhammad; Munasari Solo, Dian (Universitas Halu Oleo, 2023)
Stunting is a condition of impaired growth in children due to chronic malnutrition, especially during the first one thousand days of life (from pregnancy to the age of 2 years). Stunting is characterized by a child's height being shorter than the standard for a particular age. Awareness campaigns for the prevention of stunting must be continuously conducted, as the prevalence of stunting in Indonesia, particularly in Konawe regency, is still relatively high. According to the 2021 Indonesia Nutrition Status Survey (SSGI) data, the stunting rate in Konawe regency is 26.2%. Stunting prevention should start from before the mother gives birth until the child reaches 2 years of age. There are many factors that contribute to stunting, and it's important for the community to be aware of them. The purpose of this community service project is to raise awareness and provide understanding and knowledge to the community in the effort to prevent stunting in children and promote optimal growth. The community service activities took place in the villages of Soropia and Waworaha, Soropia district, Konawe regency, Southeast Sulawesi, targeting community groups in those villages. The activities involved lectures, the distribution of leaflets and brochures, booklets, and question-and-answer discussions with the 100 participants of the community service project. The content covered topics such as stunting, its causes, characteristics, impacts, prevention, and how to handle stunting.